(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article explains the study of Uzbek Jadid literature during the years of independence and the role of B.Kasimov’s research as a school, as a literary critic, elshunos, nationalist, Jadid scholar a participant in a major social movement called Jadidism and a critical researcher.